PENGARUH MATA KULIAH KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA KEBIDANAN DAN KEGURUAN DI KOTA TERNATE - Ibrahim, Irma; Husen, Bahrun; Ati, Sarmina (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The increasing number of unemployed graduates in Indonesia illustrates the weak absorption capacity of the labor market. One solution is to cultivate an entrepreneurial spirit from the university level. This study aims to describe the influence of entrepreneurship courses on the entrepreneurial motivation of midwifery and education students in Ternate City. The research employed a descriptive qualitative approach with 40 student participants from Cahwala Midwifery Academy of North Maluku and ISDIK Kie Raha of North Maluku. Data were collected through interviews, observations, questionnaires, and documentation, and analyzed using data reduction, presentation, and conclusion drawing techniques, as well as source triangulation. The findings reveal that entrepreneurship courses positively influence students’ motivation to engage in entrepreneurship. Students reported feeling more confident, creative, and encouraged to develop businesses based on local potential. This study highlights the importance of optimizing practical entrepreneurship learning to support graduates’ readiness to become young entrepreneurs.